Identification of Sand Mineral Content at Beach Tourist Attractions in Sampang Regency through X-Ray Fluorescence and X-Ray Diffraction Testing - Idon Joni; Sandi Vikki Ariyanto (Universitas Andalas, 2021)
Research on the natural mineral content in Sampang Regency has been conducted, namely Camplong Beach, Nepa Beach, and Mandangin Island. The XRF results show that the silica mineral content in Camplong sand at a depth of 0.5 m, 1 m, and 1.5 m are 54.6%, 53.2%, and 57.0%, respectively. Nepa sand shows the highest mineral content is calcium. The calcium content at a depth of 0.5 m, 1 m, and 1.5 m are 51.7%, 58.3%, and 63.0%, respectively. Mandangin Island sand shows the highest calcium content that are 94.69%, 94.65%, and 94.98%, at a depth of 0.5 m, 1 m, and 1.5 m, respectively. XRD test results show that in Camplong sand at a depth of 0.5 m, 1 m, and 1.5 m, SiO2 phase < 94% is formed. In Nepa sand at a depth of 0.5 m, 1 m, and 1.5 m, the SiO2 phase < 80% is formed. For Mandangin Island beach sand with a depth of 0.5 m, 1 m, and 1.5 m, the CaCO3 phase > 90% is formed. This study's results can determine the mineral content of sand, which can be used as a high-tech material to minimize illegal mining.